IMPLEMENTASI FRAMEWORK FLUTTER APLIKASI PEMBUKUAN PENGHASILAN TOKO RUMAH REZEKI KARPET BERBASIS ANDROID - Sumarni, Aprida; Annurrullah Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2022)
Bookkeeping is where the actors run a business which is indispensable in a good bookkeeping system, with this bookkeeping system business actors can find out the advantages and disadvantages of the business being run. as well as entrepreneurs can set their business strategies in the future and show the development of the business they are living. Currently, Android is known as a very complete technology or a complete package in developing a smartphone operating system that has been widely used by many people at this time. With the support of software that can be used to develop an application, namely android studio, android studio is software that has features that make it easy for users to build android applications, flutter is also called a programming language used to create software, XAMMP is a software tool that supports multiple systems namely databases. In this study, the testing method used is black box testing, which is a functional test that we can use without having to know the program or internal code structure. What is generated in an application is a flutter system framework for an android-based income-saving shop-house income accounting application that can be used by shop heads. As for the benefits of this technology, so that the head of the shop can do the bookkeeping of the income earned on the business undertaken by using an Android-based smartphone in order to make it easier for the bookkeeping. Keywords: Bookkeeping, Android, flutter , Xammp, Android Studio.